" Effects of bilingual and peer-tutoring instructional strategies on pre-service teachers' attitude Yoruba translation. " (2016)
Translation is an important aspect of Yoruba language studies and a compulsory course for pre-service teachers in colleges of education in Nigeria. As valuable as it is, reports show that students ’ attitude towards it has been negative thus leading to gross under-achievement in questions relating to translation among them. This has been traced to ineffective strategies adopted in teaching translation to pre-service teachers which do not allow them to be actively involved in the teaching-learning process. There is the need to adopt strategies that cater for these deficiencies. Among the strategies are bilingual and peer-tutoring which are learner- centered and activity-based. Studies have shown that these strategies were effective in teaching social studies and mathematics but their effect in teaching and learning of Yoruba translation has not enjoyed much research attention. Therefore, this study examined the effects of bilingual and peer-tutoring instructional strategies on pre-service teachers' attitude towards Yoruba translation. Moderating effects of students ’ verbal ability and gender were also examined. Seven hypotheses, tested at 0.05 significant level, were formulated and 300 pre-service teachers in intact classes from six purposively selected colleges of education in Southwestern Nigeria, who were randomly assigned to treatment groups served as participants. Pre-service Teachers ’ Attitude to Yoruba Translation Questionnaire (r=0.76), Students' Verbal Ability Test (r=0.78) and Instructional Guides were used as instruments. Data were analyzed using Analysis of Covariance and Scheffe post-hoc analysis. Findings show that bilingual and peer-tutoring instructional strategies are more facilitative in fostering pre-service teachers' attitude towards translation in Yoruba than the traditional lecture strategy. Hence, Yoruba translation teachers in colleges of education should adopt these strategies in teaching Yoruba translation.